Corporate market value and intangible assets of Malaysian companies / Ridzwan Bakar - Bakar, Ridzwan (2008)
The new economy has shifted the value of firms from traditionally dominated by tangible assets to intangible assets. However, thus far studies in Malaysia provide little evidence to support Malaysian companies' intangible assets position. Realizing the gap, the prime objective of this study is to examine the position of intangible assets in Malaysian -market. In particular, this study attempts to answer four research questions : (i) What is the pattern of intangible assets value of Malaysian firms? (ii) Does capital market value intangible assets higher than tangible assets? (iii) Which industry (sector) in the Bursa Malaysia (formerly known as Kuala Lumpur Stock Exchange), provides greater intangible asset value? and (iv) Do firms with higher intangible assets value, produce better financial performance? This study empirically investigates intangible assets, employing capital market accounting-based research (cross-sectional multi-regression study). The balance sheet identity model is adopted to test corporate market value and intangible assets relationship. Three models (NAnE, NAnED and Net Asset) are employed to empirically test seven hypotheses. These hypotheses have been proposed to be tested using a sample of 2,396 firm-year observations covering the period of 2000-2006. The empirical test of this study is divided into three groups namely Market Intangible Portfolio (MIP), Industry Intangible Portfolio (IIP) and Market Return Portfolio (MRP). The findings of MIP suggest that Malaysian market has developed intangible assets at a slow pace with significant presence from the year 2004 onwards. The result provides further evidence that net asset has been declining, while intangible assets and earnings are getting superior power in determining corporate market value of Malaysian market. The results from IIP indicate that two industries that is Consumer Products and Trading & Services industries have reported significant presence of intangible assets. Consumer Products industry has developed most intangible assets (value) compared to other industries. Finally, the MRP findings provide evidence that Malaysian firms with higher intangible assets produce better financial performance measured by return on equity (ROE). This study highlights the importance of intangible assets as corporate strategic assets and should draw deep interest to corporate managers, investors, regulators, accounting standard setters and researchers in financial reporting and capital market.